Kinetic determination of Image (−)malic acid in wines using sequential injection analysis - Segundo, Marcela A. (2011)
In the present work a sequential injection system for the enzymatic determination of Image (−)malic acid in wines is described. The determination was based on the detection of NADH, formed by oxidation of Image -malate to oxaloacetate, catalysed by Image -malate dehydrogenase. A kinetic method was implemented by stopping the flow when a solution plug containing sample, NAD+ and enzyme reached the detector. The rate of reaction was measured by monitoring absorbance changes at 340 nm during a fixed period of time. A linear calibration curve (rate of reaction versus concentration) was obtained for concentrations of Image (−)malic acid between 0.01 and 0.15 g l−1. The determination rate was about 22 h−1 and samples were diluted 25 or 50 times before introduction to the system. Results obtained from 16 wine samples were comparable to those obtained by the reference method.